CD64 plays a key role in diabetic wound healing - Zhang, Xiuqin; Yuan, Liuhong; Tan, Zhenyu; Wu, Huiyan; Chen, Feier; Huang, Junjie; Wang, Pengjun; Hambly, Brett D.; Bao, Shisan; Tao, Kun (Frontiers in Immunology, 2024)
Wound healing poses a clinical challenge in diabetes mellitus (DM) due to compromised host immunity. CD64, an IgG-binding Fcgr1 receptor, acts as a pro-inflammatory mediator. While its presence has been identified in various inflammatory diseases, its specific role in wound healing, especially in DM, remains unclear. Objectives: We aimed to investigate the involvement of CD64 in diabetic wound healing using a DM animal model with CD64 KO mice. Methods: First, we compared CD64 expression in chronic skin ulcers from human DM and non DM skin. Then, we monitored wound healing in a DM mouse model over 10 days, with or without CD64 KO, using macroscopic and microscopic observations, as well as immunohistochemistry. Results: CD64 expression was significantly upregulated (1.25-fold) in chronic ulcerative skin from DM patients compared to non-DM individuals. Clinical observations were consistent with animal model findings, showing a significant delay in wound healing, particularly by day 7, in CD64 KO mice compared to WT mice. Additionally, infiltrating CD163+ M2 macrophages in the wounds of DM mice decreased significantly compared to non-DM mice over time. Delayed wound healing in DM CD64 KO mice correlated with the presence of inflammatory mediators. Conclusions: CD64 seems to play a crucial role in wound healing, especially in DM conditions, where it is associated with CD163+ M2 macrophage infiltration. These data suggest that CD64 relies on host immunity during the wound healing process. Such data may provide useful information for both basic scientists and clinicians to deal with diabetic chronic wound healing.